2010
DOI: 10.1164/rccm.200906-0897oc
|View full text |Cite
|
Sign up to set email alerts
|

Spirometric Lung Function in School-Age Children

Abstract: Rationale: Few studies have investigated childhood respiratory outcomes of intrauterine growth retardation (IUGR), and it is unclear if catch-up growth in these children influences lung function. Objectives: We determined if lung function differed in 8-to 9-yearold children born at term with or without growth retardation, and, in the growth-retarded group, if lung function differed between those who did and those who did not show weight catch up. Methods: Caucasian singleton births of 37 weeks or longer gestat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(55 citation statements)
references
References 25 publications
3
52
0
Order By: Relevance
“…There is increasing evidence that prenatal factors, such as nutritional supply, permanently influence pivotal processes of lung development and maturation of pulmonary structures [9,10]. The pathogenic mechanisms that results in an impairment of lung function observed in IUGR-associated lung disease are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing evidence that prenatal factors, such as nutritional supply, permanently influence pivotal processes of lung development and maturation of pulmonary structures [9,10]. The pathogenic mechanisms that results in an impairment of lung function observed in IUGR-associated lung disease are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is an increasing body of evidence that IUGR induces changes in the developing lung with a persisting impairment of pulmonary structure and function [7][8][9]. In addition, recent epidemiological studies have demonstrated impaired lung function with reduced forced expiratory volume (FEV 1 ) in young infants following IUGR [10].…”
Section: Introductionmentioning
confidence: 99%
“…This association might either be due to an increased soluble antiangiogenic factor [15], or a congenital reduction in airways calibre and compliance in particular in infants with intrauterine growth restriction [16]. However, no studies have evaluated a possible long-term association between maternal preeclampsia and asthma or lung function in offspring.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 A recent study reported that school-aged children who specifically met the criteria for IUGR as newborns based on birth weight and Ponderal index also showed poorer lung function as compared with age-matched controls. 18 …”
Section: Discussionmentioning
confidence: 99%